Hybrid crowns - bonding protocols and shear bond strength - Epperson Matthew; Vazirani Neha; Armbruster Paul C.; Kee Edwin L.; Xu Xiaoming; Ballard Richard W. (Sciendo, 2017)
The objective of the present study was to evaluate the effect of three different surface treatment protocols on the shear bond strength (SBS) of metal brackets to Vita Enamic® and Lava™ Ultimate CAD/CAM hybrid ceramics.